2021
DOI: 10.3390/magnetochemistry7020027
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surface Effects in the Vibrational Density of States and the Vibrational Entropy in Spin Crossover Nanomaterials: A Molecular Dynamics Investigation

Abstract: Size reduction effects on the lattice dynamics of spin crossover (SCO) thin films have been investigated through molecular dynamics (MD) simulations of the density of vibrational states. The proposed simple model structure and reduced force field allows us to obtain good orders of magnitude of the sound velocity in both spin states and takes into account the contribution of free surfaces in the vibrational properties of very thin films (below a thickness of 12 nm). The slab method issue from the field of surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…We note here that the interfacial energy is considered negligible in comparison with the surface energy for a semi‐coherent interface and this term will be thus omitted. In a recent work, [ 50 ] we have shown that the surface entropy difference (per molecule) Δ S s was negligible in the case of this modeled structure. The contribution of solid–solid interface to the entropy is more difficult to estimate, but we can reasonably assume that Δ S int ( L z ) ≈ 0 in this work since a semi‐coherent interface between two phases having similar mechanical and structural properties are considered, so that the production of configurational entropy is limited.…”
Section: Methodology and Computational Detailsmentioning
confidence: 64%
See 4 more Smart Citations
“…We note here that the interfacial energy is considered negligible in comparison with the surface energy for a semi‐coherent interface and this term will be thus omitted. In a recent work, [ 50 ] we have shown that the surface entropy difference (per molecule) Δ S s was negligible in the case of this modeled structure. The contribution of solid–solid interface to the entropy is more difficult to estimate, but we can reasonably assume that Δ S int ( L z ) ≈ 0 in this work since a semi‐coherent interface between two phases having similar mechanical and structural properties are considered, so that the production of configurational entropy is limited.…”
Section: Methodology and Computational Detailsmentioning
confidence: 64%
“…The investigation of lattice dynamical properties has been carried out in both spin states through the calculation of the total density of vibrational states (vDOS) on a slab having a thickness of ≈13 nm (2500 octahedrons) in the framework of the model I. This thickness has been shown to be sufficiently large to model the vibrational properties of a bulk material, [ 50 ] avoiding the discretization of the vDOS spectrum related to confinement effects. The slab adapted method assures the absence of surface effects.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations